Hypothesis and Theory: Revisiting Views on the Co-evolution of the Melanocortin Receptors and the Accessory Proteins, MRAP1 and MRAP2 - Dores, Robert M. (Frontiers in Endocrinology, 2016)
The evolution of the melanocortin receptors (MCRs) is closely associated with the evolution of the melanocortin-2 receptor accessory proteins (MRAPs). Recent annotation of the elephant shark genome project revealed the sequence of a putative MRAP1 ortholog. The presence of this sequence in the genome of a cartilaginous fish raises the possibility that the mrap1 and mrap2 genes in the genomes of gnathostome vertebrates were the result of the chordate 2R genome duplication event. The presence of a putative MRAP1 ortholog in a cartilaginous fish genome is perplexing. Recent studies on melanocortin-2 receptor (MC2R) in the genomes of the elephant shark and the Japanese stingray indicate that these MC2R orthologs can be functionally expressed in CHO cells without co-expression of an exogenous mrap1 cDNA. The novel ligand selectivity of these cartilaginous fish MC2R orthologs is discussed. Finally, the origin of the mc2r and mc5r genes is reevaluated. The distinctive primary sequence conservation of MC2R and MC5R is discussed in light of the physiological roles of these two MCR paralogs.